2015
DOI: 10.1038/ki.2014.118
|View full text |Cite
|
Sign up to set email alerts
|

Shifting paradigms in eligibility criteria for live kidney donation: a systematic review

Abstract: As the organ shortage increases, inherently the demand for donor kidneys continues to rise. Thus, live kidney donation is essential for increasing the donor pool. In order to create successful expansion, extended criteria live kidney donors should be considered. This review combines current guidelines with all available literature in this field, trying to seek and establish the optimal extended criteria. Comprehensive searches were carried out in major databases until November 2013 to search for articles regar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 105 publications
0
75
0
Order By: Relevance
“…By contrast, in this same time period, LKD has increased 2% per year for those aged $50 years. Importantly, older donors do not appear to be at any heightened risk of poor outcomes after donation (52), and LDKT outcomes from older living donors are comparable to receiving a kidney from a deceased standard criteria donor (53). Research is needed to examine the underlying mechanism for the shift in living donor age and whether it persists after implementation of the new kidney allocation system.…”
Section: Agementioning
confidence: 99%
“…By contrast, in this same time period, LKD has increased 2% per year for those aged $50 years. Importantly, older donors do not appear to be at any heightened risk of poor outcomes after donation (52), and LDKT outcomes from older living donors are comparable to receiving a kidney from a deceased standard criteria donor (53). Research is needed to examine the underlying mechanism for the shift in living donor age and whether it persists after implementation of the new kidney allocation system.…”
Section: Agementioning
confidence: 99%
“…For example, a systematic analysis of 22 studies found no real difference in outcomes in grafts from older donors compared with those from younger donors. 11 However, other studies have shown poorer graft outcomes, which were associated with higher levels of complications. 8 With increasing demand for organs, longer wait times, and more frequent deaths when waiting for organs, this lack of consensus promotes elderly kidney donation.…”
Section: Discussionmentioning
confidence: 85%
“…[7][8][9] During the early stages of living-donor kidney programs, advanced age was widely considered as an absolute contraindication, mainly as it was deemed to increase long-term morbidity and mortality. 10,11 Patients with advanced age also were more likely to be excluded from donation because of the presence of comorbidities. 11 To minimize both short-term and long-term complications, an extensive donor work-up is performed before donation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, when living donation was first introduced only relatively young and healthy individuals were accepted for kidney donation. As the criteria for donation have expanded to include older donors and those with comorbidities, 44 however, the current donor population is now demographically different from the cohort for whom long term follow-up data are available. This limits the generalisability of findings from studies of early donor populations to currently accepted donors.…”
Section: Longer Term Risksmentioning
confidence: 99%